Connection method for brazing hard alloy and stainless steel by using porous alloy interlayer

By brazing the porous alloy intermediate layer in the connection between cemented carbide and stainless steel, the problem of high residual stress and easy cracking caused by the difference in thermal expansion coefficient of the welded joint is solved, and the mechanical properties of the joint are improved.

CN119347024AInactive Publication Date: 2025-01-24YONGZHOU PROD QUALITY SUPERVISION & INSPECTION INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411470262.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The thermal expansion coefficients of cemented carbide and stainless steel are very different, resulting in the problems of large residual stress and prone to cracking of the welded joints.

Method used

The porous alloy intermediate layer is used for brazing, and the brazing is completed by heating to 780°C to 980°C in a vacuum brazing furnace, applying welding pressure, and cooling to room temperature.

Benefits of technology

It reduces the production and residual stress of the brittle compounds of the welding joint, improves the mechanical properties of the joints, and solves the problem of welding problems caused by the difference in thermal expansion coefficients of hard alloy and stainless steel.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a connecting method for brazing a hard alloy and stainless steel by using a porous alloy interlayer. The method comprises the following steps: (1) assembling, namely removing oxidation films and oil stains on the surfaces of hard alloy and stainless steel by using mechanical polishing and chemical cleaning, and ultrasonically cleaning the Ni-Cu-Cr porous alloy intermediate layer obtained in the step (1), the hard alloy and the stainless steel; the Ni-Cu-Cr porous alloy intermediate layer is an intermediate layer used for brazing hard alloy and stainless steel, nickel-copper active brazing filler metal serves as the basis, the chromium element is added in a compounded mode to modify the alloy brazing filler metal, nickel is a strengthening element, solid solution strengthening can be achieved through the nickel and the copper element, the abrasion resistance of the alloy brazing filler metal is improved, and the service life of the alloy brazing filler metal is prolonged. The nickel element and the chromium element can be infinitely dissolved with the iron element, so that the strength of the joint is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dissimilar material connection, and in particular to a method for connecting hard alloy and stainless steel by brazing with a porous alloy intermediate layer. Background Art

[0002] Cemented carbide has the advantages of extremely high hardness, wear resistance and good thermal conductivity, but its disadvantage is that its toughness and processability are poor. Therefore, cemented carbide is often connected with relatively cheap steel with excellent mechanical properties. Among them, the complex components formed by cemented carbide and stainless steel are widely used in projects such as oil drilling, mining and space exploration. The brazing method is used to connect cemented carbide and stainless steel, which has the advantages of relatively stable metallurgical bonding and high mechanical properties. However, the thermal expansion coefficients of cemented carbide and stainless steel are very different, resulting in large residual stress and easy cracking in the welded joint. Adding an intermediate layer for brazing can relieve the residual stress of the joint and improve the connection strength of the welded joint, which has practical application research prospects. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a method for connecting cemented carbide and stainless steel by brazing using a porous alloy intermediate layer, so as to solve the problems raised in the above background technology.

[0004] The present invention solves the technical problem by adopting the following technical solution:

[0005] The present invention provides a method for connecting hard alloy and stainless steel by brazing with a porous alloy intermediate layer, comprising the following steps:

[0006] 1. Preparation of porous alloy intermediate layer:

[0007] 2. Brazing connection:

[0008] (1) Assembly

[0009] Mechanical grinding and chemical cleaning are used to remove the oxide film and oil stains on the surfaces of the cemented carbide and the stainless steel, and then the Ni-Cu-Cr porous alloy intermediate layer, the cemented carbide and the stainless steel obtained in step 1 are ultrasonically cleaned, and then the Ni-Cu-Cr porous alloy intermediate layer, the cemented carbide, the stainless steel and the brazing filler metal are assembled to obtain an assembled component;

[0010] (2) Brazing connection: The assembled components obtained in step 2 are placed in a vacuum brazing furnace, and the vacuum degree in the vacuum brazing furnace is reduced to 1×10 -3 Pa, then heat to 780℃~980℃ at a heating rate of 10~15℃ / min and keep warm for 10~20min, apply 0.1~1MPa welding pressure, and then cool to room temperature with the furnace to complete the brazing.

[0011] Preferably, the specific steps of preparing the porous alloy intermediate layer are:

[0012] (1) Weighing raw materials: a binder, a surfactant, a plasticizer, and ethanol are weighed in a mass ratio of 1:1:1:6-12 to obtain a mixed slurry, and weighing appropriate amounts of Ni powder, Cu powder, and Cr powder to obtain a metal mixed powder;

[0013] (2) Slurry mixing: The mixed slurry and metal powder are placed in a sealed container and then mixed in a powder mixer for 10 to 24 hours to obtain a uniform slurry;

[0014] (3) Scraping: Scrape the slurry evenly on a stainless steel plate or glass plate using a scraper, with a thickness of 200 to 1000 um;

[0015] (4) Drying: Place the stainless steel plate or glass plate in a nitrogen atmosphere and dry it for 2 to 3 hours, then take the film and keep it in a constant temperature vacuum drying oven at 60 to 80°C for 1 hour with a vacuum degree of 1×10-1Mpa to remove alcohol and water vapor;

[0016] (5) Debonding and sintering process.

[0017] Preferably, the specific steps of the degumming and sintering process are:

[0018] The film is placed in a vacuum sintering furnace, and the temperature of the vacuum molybdenum sheet sintering furnace is increased to 200°C to 300°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 200°C to 300°C for 60 to 360 minutes;

[0019] Then, the temperature is raised to 350°C to 400°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 350°C to 400°C for 60 to 360 minutes;

[0020] Then, the temperature is increased to 450°C to 500°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 450°C to 500°C for 60 to 360 minutes. Then, the temperature is increased to 800°C to 950°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 800°C to 950°C for 60 to 240 minutes. After the insulation, the temperature is reduced to 500°C to 700°C at a cooling rate of 1°C / min to 5°C / min.

[0021] The temperature is kept at 500℃~700℃ for 60~360min. After the heat preservation, the power of the vacuum molybdenum sheet sintering furnace is turned off, and the sheet is cooled to room temperature with the furnace to obtain a porous alloy intermediate layer with a certain toughness, which is cut and rolled as needed.

[0022] Preferably, in step 1, the Ni, Cu and Cr metal powders are all spherical powders with a particle size of 1 to 100 microns and a purity higher than 99.9%. The mass fraction of Ni powder is 35% to 45%, the mass fraction of Cu powder is 35% to 45%, and the rest is Cr powder.

[0023] Preferably, the ratio of the mixed slurry to the metal powder in step 1 is determined according to the particle size of the metal powder and can be adjusted to 1:3 to 1:6.

[0024] Preferably, in step 2, the cemented carbide, stainless steel, porous alloy intermediate layer and solder are assembled in the order of cemented carbide, solder, Ni-Cu-Cr porous alloy intermediate layer, solder and stainless steel.

[0025] Preferably, the solder in step 2 is any combination of silver-based solder, copper-based solder and nickel-based solder.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The intermediate layer of the present invention for brazing cemented carbide and stainless steel has a brazing temperature range of 780 to 980°C, is soft and tough, has a smooth surface, and can be controlled to have a thickness of 100 to 600 microns. It can be curled for storage and punched into any shape, and can solve the problems of large difference in thermal expansion coefficients between cemented carbide and stainless steel, large residual stress in welded joints, and easy cracking, thereby improving the mechanical properties of the joints, smoothly achieving the connection between cemented carbide and stainless steel, and obtaining high-quality welded joints. The brazed joints produce less brittle compounds, low residual stress, and can be used for brazing in a variety of occasions. The intermediate layer of the present invention is suitable for brazing connections between various stainless steel materials and dissimilar materials such as tungsten-cobalt cemented carbide;

[0028] The Ni-Cu-Cr porous alloy intermediate layer in the present invention is an intermediate layer for brazing hard alloy and stainless steel. It is based on nickel-copper active brazing filler metal, and the alloy brazing filler metal is modified by composite addition of chromium element, wherein nickel is a strengthening element, and can achieve solid solution strengthening with copper element, improve the wear resistance of the alloy brazing filler metal, and nickel element and chromium element can infinitely solid dissolve with iron element, improve the strength of the joint. The prepared porous alloy intermediate layer is soft and tough, with a smooth surface, and the thickness can be controlled to be 100 to 600 microns, and can be curled for storage and punched into any shape. The brazing filler metal has the characteristics of good wettability, low melting point, brazing temperature range of 800 to 980°C, good joint shear resistance and good wear resistance.

[0029] The Ni-Cu-Cr porous alloy intermediate layer prepared by the mechanical metallurgical alloying method of the present invention has the advantages of low energy consumption, simple operation, high production efficiency and easy control of alloy composition and dosage, etc., can be well adapted to different brazing joint shapes, and the thickness during use is controlled by scraping film thickness or rolling, which is convenient for controlling the usage amount. The preparation method has a simple process flow and is conducive to mass production.

[0030] The Ni-Cu-Cr porous alloy intermediate layer of the present invention is applied to the composite material prepared by brazing YG6 hard alloy and 304 stainless steel, and has a good effect, and the shear strength of the joint reaches 465.56-601.32MPa. DETAILED DESCRIPTION

[0031] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The method for connecting cemented carbide and stainless steel by brazing with a porous alloy intermediate layer in this embodiment comprises the following steps:

[0033] 1. Preparation of porous alloy intermediate layer:

[0034] 2. Brazing connection:

[0035] (1) Assembly

[0036] Mechanical grinding and chemical cleaning are used to remove the oxide film and oil stains on the surfaces of the cemented carbide and the stainless steel, and then the Ni-Cu-Cr porous alloy intermediate layer, the cemented carbide and the stainless steel obtained in step 1 are ultrasonically cleaned, and then the Ni-Cu-Cr porous alloy intermediate layer, the cemented carbide, the stainless steel and the brazing filler metal are assembled to obtain an assembled component;

[0037] (2) Brazing connection: The assembled components obtained in step 2 are placed in a vacuum brazing furnace, and the vacuum degree in the vacuum brazing furnace is reduced to 1×10 -3 Pa, then heat to 780℃~980℃ at a heating rate of 10~15℃ / min and keep warm for 10~20min, apply 0.1~1MPa welding pressure, and then cool to room temperature with the furnace to complete the brazing.

[0038] The specific steps for preparing the porous alloy intermediate layer of this embodiment are as follows:

[0039] (1) Weighing raw materials: a binder, a surfactant, a plasticizer, and ethanol are weighed in a mass ratio of 1:1:1:6-12 to obtain a mixed slurry, and weighing appropriate amounts of Ni powder, Cu powder, and Cr powder to obtain a metal mixed powder;

[0040] (2) Slurry mixing: The mixed slurry and metal powder are placed in a sealed container and then mixed in a powder mixer for 10 to 24 hours to obtain a uniform slurry;

[0041] (3) Scraping: Scrape the slurry evenly on a stainless steel plate or glass plate using a scraper, with a thickness of 200 to 1000 um;

[0042] (4) Drying: Place the stainless steel plate or glass plate in a nitrogen atmosphere and dry it for 2 to 3 hours, then take the film and keep it in a constant temperature vacuum drying oven at 60 to 80°C for 1 hour with a vacuum degree of 1×10-1Mpa to remove alcohol and water vapor;

[0043] (5) Debonding and sintering process.

[0044] The specific steps of the degumming and sintering process of this embodiment are:

[0045] The film is placed in a vacuum sintering furnace, and the temperature of the vacuum molybdenum sheet sintering furnace is increased to 200°C to 300°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 200°C to 300°C for 60 to 360 minutes;

[0046] Then, the temperature is raised to 350°C to 400°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 350°C to 400°C for 60 to 360 minutes;

[0047] Then, the temperature is increased to 450°C to 500°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 450°C to 500°C for 60 to 360 minutes. Then, the temperature is increased to 800°C to 950°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 800°C to 950°C for 60 to 240 minutes. After the insulation, the temperature is reduced to 500°C to 700°C at a cooling rate of 1°C / min to 5°C / min.

[0048] The temperature is kept at 500℃~700℃ for 60~360min. After the heat preservation, the power of the vacuum molybdenum sheet sintering furnace is turned off, and the sheet is cooled to room temperature with the furnace to obtain a porous alloy intermediate layer with a certain toughness, which is cut and rolled as needed.

[0049] In step 1 of this embodiment, the Ni, Cu and Cr metal powders are all spherical powders with a particle size of 1 to 100 microns and a purity higher than 99.9%. The mass fraction of Ni powder is 35% to 45%, the mass fraction of Cu powder is 35% to 45%, and the rest is Cr powder.

[0050] In step 1 of this embodiment, the ratio of the mixed slurry to the metal powder is determined according to the particle size of the metal powder and can be adjusted to 1:3 to 1:6.

[0051] In step 2 of this embodiment, the cemented carbide, stainless steel, porous alloy middle layer and solder are assembled in the order of cemented carbide, solder, Ni-Cu-Cr porous alloy middle layer, solder and stainless steel.

[0052] The solder described in step 2 of this embodiment is any combination of silver-based solder, copper-based solder and nickel-based solder.

[0053] Example 1

[0054] The Ni-Cu-Cr porous alloy intermediate layer described in this embodiment is prepared from a mixed metal powder including nickel powder, copper powder, and chromium powder, and is composed of the following mass percentages: nickel powder accounts for 45%, copper powder accounts for 40%, and chromium powder accounts for 15%;

[0055] The specific preparation method of the Ni-Cu-Cr porous alloy intermediate layer is as follows:

[0056] (1) Take 48 micron Ni powder, Cu powder and Cr powder respectively according to the above ratio.

[0057] (2) PVB, Tween-20, PEG and alcohol were weighed in a mass ratio of 1:1:1:6 respectively.

[0058] (3) The powder in step (1) and the organic matter in step (2) are weighed in a mass ratio of 5:1, placed in a V-type powder mixer and mechanically mixed for 18 hours to obtain a paste-like solder.

[0059] (4) The paste solder in step (3) is evenly scraped onto a stainless steel plate or a glass plate with a scraper to a thickness of 400 μm. The stainless steel plate is placed in a nitrogen atmosphere and dried for 2 h before the film is taken out. The film is then kept in a constant temperature vacuum drying oven at 70° C. for 1 h at a vacuum degree of 1×10-1 MPa to remove alcohol and moisture, thereby obtaining a porous alloy intermediate layer that has not yet been debonded.

[0060] (5) The membrane is placed in a vacuum sintering furnace, and the temperature is increased to 250°C at a heating rate of 5°C / min, and the film is kept at 250°C for 180 min. The film is then heated to 400°C at a heating rate of 2°C / min, and the film is kept at 400°C for 240 min. The film is then heated to 500°C at a heating rate of 2°C / min, and the film is kept at 500°C for 180 min. The film is then heated to 900°C at a heating rate of 5°C / min, and the film is kept at 900°C for 120 min. After the heat preservation, the film is cooled to 600°C at a cooling rate of 5°C / min, and the film is kept at 600°C for 120 min. After the heat preservation, the film is turned off and cooled to room temperature with the furnace to obtain a porous alloy intermediate layer with a certain toughness, which is cut and rolled as needed.

[0061] (6) Mechanical grinding and acetone are used to remove the oxide film and oil stains on the surface of cemented carbide and stainless steel, and the Ni-Cu-Cr porous alloy intermediate layer, cemented carbide and stainless steel are ultrasonically cleaned. Then, the cemented carbide, HYAg40Ni brazing filler metal, Ni-Cu-Cr porous alloy intermediate layer, HYAg40Ni brazing filler metal and stainless steel are assembled in this order to obtain assembled components. The assembled components are placed in a vacuum brazing furnace, and the vacuum degree in the vacuum brazing furnace is evacuated to below 1×10-3Pa. The components are then heated to 800°C at a heating rate of 10°C / min and kept warm for 10 minutes. A welding pressure of 0.4MPa is applied, and then the components are cooled to room temperature with the furnace to complete the brazing.

[0062] The average shear strength of the joint obtained by brazing YG6 cemented carbide and 304 stainless steel in this embodiment is 553.63 MPa.

[0063] Example 2

[0064] The Ni-Cu-Cr porous alloy intermediate layer described in this embodiment is prepared from a mixed metal powder including nickel powder, copper powder, and chromium powder, and is composed of the following mass percentages: nickel powder accounts for 45%, copper powder accounts for 35%, and chromium powder accounts for 20%;

[0065] The specific preparation method of the Ni-Cu-Cr porous alloy intermediate layer is as follows:

[0066] (1) Take 20 micron Ni powder, Cu powder and Cr powder respectively according to the above ratio.

[0067] (2) PVB, Tween-20, PEG and alcohol were weighed in a mass ratio of 1:1:1:10.

[0068] (3) The powder in step (1) and the organic matter in step (2) are weighed in a mass ratio of 4:1, placed in a V-type powder mixer and mechanically mixed for 20 hours to obtain a paste-like solder.

[0069] (4) The paste solder in step (3) is evenly scraped onto a stainless steel plate or a glass plate with a scraper to a thickness of 400 μm. The stainless steel plate is placed in a nitrogen atmosphere and dried for 2 h before the film is taken out. The film is then kept in a constant temperature vacuum drying oven at 70° C. for 1 h at a vacuum degree of 1×10-1 MPa to remove alcohol and moisture, thereby obtaining a porous alloy intermediate layer that has not yet been debonded.

[0070] (5) The membrane is placed in a vacuum sintering furnace, and the temperature is increased to 250°C at a heating rate of 5°C / min, and kept at 250°C for 180 minutes. The temperature is then increased to 400°C at a heating rate of 2°C / min, and kept at 400°C for 240 minutes. The temperature is then increased to 500°C at a heating rate of 2°C / min, and kept at 500°C for 180 minutes. The temperature is then increased to 800°C at a heating rate of 5°C / min, and kept at 800°C for 120 minutes. After the insulation is completed, the temperature is then reduced to 600°C at a cooling rate of 5°C / min, and kept at 600°C for 120 minutes. After the insulation is completed, the power of the vacuum molybdenum sheet sintering furnace is turned off, and the film is cooled to room temperature with the furnace to obtain a porous alloy intermediate layer with a certain toughness, which is cut and rolled as needed.

[0071] (6) Mechanical grinding and acetone were used to remove the oxide film and oil stains on the surface of cemented carbide and stainless steel, and the Ni-Cu-Cr porous alloy intermediate layer, cemented carbide and stainless steel were ultrasonically cleaned. Then, the cemented carbide, HYCu58ZnMn brazing filler metal, Ni-Cu-Cr porous alloy intermediate layer, HYCu58ZnMn brazing filler metal and stainless steel were assembled in this order to obtain the assembled components. The assembled components were placed in a vacuum brazing furnace, and the vacuum degree in the vacuum brazing furnace was evacuated to below 1×10-3Pa. The components were then heated to 900°C at a heating rate of 10°C / min and kept warm for 10min. A welding pressure of 0.6MPa was applied, and the components were then cooled to room temperature with the furnace to complete the brazing.

[0072] The average shear strength of the joint obtained by brazing YG6 cemented carbide and 304 stainless steel in this embodiment is 593.26 MPa.

[0073] The present invention discloses a method for connecting hard alloy and stainless steel by brazing with a porous alloy intermediate layer, which belongs to the technical field of connecting dissimilar materials. The intermediate layer contains organic substances such as multi-component alloy powder and a binder, and the multi-component alloy powder is composed of the following components in weight percentage: 30% to 45% Ni, 30% to 45% Cu, and the balance Cr. The brazing temperature range of the porous alloy intermediate layer for brazing hard alloy and stainless steel of the present invention is 780 to 980°C, the texture is soft and tough, the surface is smooth, the thickness can be controlled to be 100 to 600 microns, it can be curled for storage and punched into any shape, and the problems of large difference in thermal expansion coefficient between hard alloy and stainless steel, large residual stress of joint and easy cracking can be solved, the mechanical properties of the joint can be improved, the connection between hard alloy and stainless steel can be smoothly realized, and a high-quality welding joint can be obtained.

[0074] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for connecting cemented carbide and stainless steel by brazing a porous alloy intermediate layer, characterized in that: The steps include:

1. Preparation of porous alloy intermediate layer:

2. Brazing connection: (1) Assembly Mechanical grinding and chemical cleaning are used to remove the oxide film and oil stains on the surfaces of the cemented carbide and the stainless steel, and then the Ni-Cu-Cr porous alloy intermediate layer, the cemented carbide and the stainless steel obtained in step 1 are ultrasonically cleaned, and then the Ni-Cu-Cr porous alloy intermediate layer, the cemented carbide, the stainless steel and the brazing filler metal are assembled to obtain an assembled component; (2) Brazing connection: The assembled components obtained in step 2 are placed in a vacuum brazing furnace, and the vacuum degree in the vacuum brazing furnace is reduced to 1×10 -3 Pa, then heat to 780℃~980℃ at a heating rate of 10~15℃ / min and keep warm for 10~20min, apply 0.1~1MPa welding pressure, and then cool to room temperature with the furnace to complete the brazing.

2. The method for connecting cemented carbide and stainless steel by brazing with a porous alloy intermediate layer according to claim 1, characterized in that: The specific steps for preparing the porous alloy intermediate layer are: (1) Weighing raw materials: a binder, a surfactant, a plasticizer, and ethanol are weighed in a mass ratio of 1:1:1:6-12 to obtain a mixed slurry, and weighing appropriate amounts of Ni powder, Cu powder, and Cr powder to obtain a metal mixed powder; (2) Slurry mixing: The mixed slurry and metal powder are placed in a sealed container and then mixed in a powder mixer for 10 to 24 hours to obtain a uniform slurry; (3) Scraping: Scrape the slurry evenly on a stainless steel plate or glass plate using a scraper, with a thickness of 200 to 1000 um; (4) Drying: Place the stainless steel plate or glass plate in a nitrogen atmosphere and dry it for 2 to 3 hours, then take the film and keep it in a constant temperature vacuum drying oven at 60 to 80°C for 1 hour with a vacuum degree of 1×10-1Mpa to remove alcohol and water vapor; (5) Debonding and sintering process.

3. The method for connecting cemented carbide and stainless steel by brazing with a porous alloy intermediate layer according to claim 2, characterized in that: The specific steps of the degumming and sintering process are: The film is placed in a vacuum sintering furnace, and the temperature of the vacuum molybdenum sheet sintering furnace is increased to 200°C to 300°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 200°C to 300°C for 60 to 360 minutes; Then, the temperature is raised to 350°C to 400°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 350°C to 400°C for 60 to 360 minutes; Then, the temperature is increased to 450°C to 500°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 450°C to 500°C for 60 to 360 minutes. Then, the temperature is increased to 800°C to 950°C at a heating rate of 1°C / min to 10°C / min, and the temperature is kept at 800°C to 950°C for 60 to 240 minutes. After the insulation, the temperature is reduced to 500°C to 700°C at a cooling rate of 1°C / min to 5°C / min. The temperature is kept at 500℃~700℃ for 60~360min. After the heat preservation, the power of the vacuum molybdenum sheet sintering furnace is turned off, and the sheet is cooled to room temperature with the furnace to obtain a porous alloy intermediate layer with a certain toughness, which is cut and rolled as needed.

4. The method for connecting cemented carbide and stainless steel by brazing with a porous alloy intermediate layer according to claim 3, characterized in that: In the step 1, the Ni, Cu and Cr metal powders are all spherical powders with a particle size of 1 to 100 microns and a purity higher than 99.9%. The mass fraction of Ni powder is 35% to 45%, the mass fraction of Cu powder is 35% to 45%, and the rest is Cr powder.

5. The method for connecting cemented carbide and stainless steel by brazing with a porous alloy intermediate layer according to claim 4, characterized in that: The ratio of the mixed slurry to the metal powder in the step 1 is determined according to the particle size of the metal powder and can be adjusted to 1:3 to 1:

6.

6. The method for connecting cemented carbide and stainless steel by brazing with a porous alloy intermediate layer according to claim 4, characterized in that: In step 2, the cemented carbide, stainless steel, porous alloy middle layer and solder are assembled in the order of cemented carbide, solder, Ni-Cu-Cr porous alloy middle layer, solder and stainless steel.

7. The method for connecting cemented carbide and stainless steel by brazing with a porous alloy intermediate layer according to claim 4, characterized in that: The solder described in step 2 is any combination of silver-based solder, copper-based solder and nickel-based solder.